2008
DOI: 10.1038/nbt1483
|View full text |Cite
|
Sign up to set email alerts
|

A drug-inducible transgenic system for direct reprogramming of multiple somatic cell types

Abstract: The study of induced pluripotency is complicated by the need for infection with high-titer retroviral vectors, which results in genetically heterogeneous cell populations. We generated genetically homogeneous ‘secondary’ somatic cells that carry the reprogramming factors as defined doxycycline (dox)-inducible transgenes. These cells were produced by infecting fibroblasts with dox-inducible lentiviruses, reprogramming by dox addition, selecting induced pluripotent stem cells and producing chimeric mice. Cells d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
387
2
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 404 publications
(417 citation statements)
references
References 28 publications
19
387
2
9
Order By: Relevance
“…We found that 8 days of dox-induced Oct4 expression was sufficient for iPSC generation observed at day 24 after transduction ( Figure 4A). Efficiency increased when Oct4 expression was induced for 12 days (Figure 4A), which is in consistent with previous reports that a greater number of iPSCs are generated when exogenous reprogramming factors were expressed for longer period of time [19,20]. However, iPSC colony numbers decreased when Oct4 was induced for more than 12 days, and most of the iPSC colonies emerged 4-8 days after dox withdrawal ( Figure 4A).…”
Section: Reprogramming Kinetics Of Mouse Fibroblasts By Doxinducible supporting
confidence: 81%
“…We found that 8 days of dox-induced Oct4 expression was sufficient for iPSC generation observed at day 24 after transduction ( Figure 4A). Efficiency increased when Oct4 expression was induced for 12 days (Figure 4A), which is in consistent with previous reports that a greater number of iPSCs are generated when exogenous reprogramming factors were expressed for longer period of time [19,20]. However, iPSC colony numbers decreased when Oct4 was induced for more than 12 days, and most of the iPSC colonies emerged 4-8 days after dox withdrawal ( Figure 4A).…”
Section: Reprogramming Kinetics Of Mouse Fibroblasts By Doxinducible supporting
confidence: 81%
“…The Brachyury-green fluorescent protein (Brachyury-GFP) ES cell line was provided by Dr. Gordon Keller (McEwen Center for Regenerative Medicine, Toronto, ON, Canada). The murine iPS cell line, NANOG-GFP2 was gifted from Prof. Rudolf Jaenisch (Whitehead Institute, Cambridge, MA) and has been described previously [21]. All chemicals, unless otherwise stated, were purchased from Sigma-Aldrich (St. Louis, MO, http://www.sigmaaldrich.com).…”
Section: Methodsmentioning
confidence: 99%
“…Secondary mouse embryonic fibroblasts (2° MEFs) were isolated from chimeric embryos as previously described 20 , providing doxycycline inducible Oct4, Sox2, Klf4, and c-Myc expression; Neomycin selection at the Nanog locus; and a fluorescent transcriptional reporter for Oct4. The parental pluripotent stem cells used to generate the secondary line were derived by replacing an Oct4 allele with an Oct4-IRES-GFP sequence in Nanog-Neo iPS cells 20 .…”
Section: Secondary Somatic Cell Generation and Reprogrammingmentioning
confidence: 99%
“…The parental pluripotent stem cells used to generate the secondary line were derived by replacing an Oct4 allele with an Oct4-IRES-GFP sequence in Nanog-Neo iPS cells 20 . Secondary MEFs were plated at optimal density 20 and passaged after 48 hours. Doxycycline (2μg/ml, Stemgent) was added 24 hours after replating, marking the start of reprogramming.…”
Section: Secondary Somatic Cell Generation and Reprogrammingmentioning
confidence: 99%